Pengembangan Media Pembelajaran Berbasis Filmora untuk Materi Drama di Kelas XI Sekolah Menengah Atas Al Washliyah Pasar Senen Medan - Risti Alya Namira; Nila Safina; Ratna Soraya (Medan Resource Center, 2025)
This study aimed to describe the development process, validation, feasibility, and effectiveness of the using of Indonesian language learning media with drama materials assisted by the Filmora Application in class XI. This study was conducted at SMA Al Washliyah Pasar Senen Medan. This study used the Research and Development (R&D) with ADDIE model developed by Lee and Owens consisting of Analysis, Design, Development, Implementation, and Evaluation with a population as 24 students. The sample in this study used a purposive sampling technique in total as 15 students. The types of data in this study include qualitative and quantitative data. The results of this study are in the form of Indonesian language learning media products with drama material assisted by the Filmora application. Based on the validation results from material expert I, the percentage as 81% or